From Mountains to the Sea: A Geo-Cultural Analysis of Climate-Driven Culinary Traditions in India - Meena, Priyanka Kumari (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
India’s culinary diversity is one of the most vivid reflections of its geographic and cultural heterogeneity. Spanning from snow-capped mountains to tropical coastlines and semi-arid plateaus, the country’s varied terrain and climate have significantly influenced not only the availability of ingredients but also the evolution of distinct cooking techniques, preservation methods, and food customs. This paper undertakes a geo-cultural analysis to explore how climatic conditions, topographical variations, and ecological factors shape regional dietary patterns across three major Indian zones: the Himalayan belt, the coastal regions, and the Deccan Plateau. Beyond physical geography, the paper also considers how these foodways intersect with cultural identities, religious practices, caste-based customs, and historical trade networks. It argues that culinary traditions in India are not static expressions of climate alone, but rather dynamic, living systems shaped by centuries of adaptation, innovation, and cultural exchange. The study ultimately contributes to a deeper understanding of how ecological realities and human agency collectively shape food culture, offering valuable insights for ongoing discussions on sustainability, food security, and cultural heritage preservation in the Indian context.